Perspectives on violent extremism from development–humanitarian NGO staff in Southeast Asia. Issue 1 (2nd January 2023) - Sonrexa, Juhi; Kelly, Leanne M.; Barton, Greg; Ware, Anthony
Abstract: Violent extremism (VE) significantly affects many contexts within which international development–humanitarian non-governmental organisations (NGOs) operate in Southeast Asia. Recent preventing/countering violent extremism (P/CVE) models highlight the need for community-based preventative activities; however, there has been little research to date examining the understandings of international development–humanitarian NGOs regarding VE in their context, and little attention paid to their views as to how development–humanitarian NGO programming might seek to address VE. This paper explores the meaning and impact of VE as understood by the Myanmar, Indonesia and Philippines country office staff of a large international NGO. Drawing on 40 interviews, the findings illustrate new understandings of VE and the role NGOs can play in shaping and improving counter-extremism strategies. This includes a proposition to broaden the conceptual focus on extremism to include expressions of hatred and intolerance that do not necessarily involve threats, physical violence or links to violent extremist networks. Additionally, the findings point to the importance of relationships between VE and women's and girls' position in society, its effect on youth, and the relationship between extremism and any extreme use of force by the state or its promotion of hate towards minority groups.